Philosophical Ethics - Matthews, George W. (Open textbook library., 2020)
This book is an introduction to philosophical ethics intended for use in introductory college or high school level courses. It has grown out of lecture notes I shared with the first students who took my online Ethics course at the Pennsylvania College of Technology almost 20 years ago. Since then it has seen more development in a variety of forms – starting out as a pdf document, and then evolving into a static set of WordPress pages and finally now as a book written in bookdown and hosted at GitHub. This text represents my attempt to scratch a couple of itches. The first is my wanting a presentation of the major philosophical approaches to ethics that I can actually agree with and that is integrated into my overall teaching method. I tend to teach philosophy to beginners and so there is a fair amount of discussion of the tools used by philosophers and of the ways in which their approach differs from that of their colleagues in other disciplines. There are of course many good quality ethics textbooks out there, and yet none has exactly matched my way of wanting to present the material. Teaching ethics over the years has been a process of active exploration and constant revision of my approach as I have come to a more nuanced and richer appreciation of what ethical thinking and theorizing is all about, as well as some ideas about how I think the main strands of argument relate to each other. Yes this is a partisan effort, but it’s all subject to revision and refinement based on, I hope at least, the better argument. That’s what I am trying to get across here. The second itch I am trying to scratch has to do with initiatives in open education, and I’d like this text to contribute in its own small way to the much larger and more influential open source movement and philosophy of which I consider it a part. Knowledge is only ours to share. Yes of course writers, developers and publishers do hard work that deserves compensation. But intellectual property, it seems to me, is a false idol that deserves to be smashed. So here is my effort to chip away at it – knowledge should free us and and not sink us into both literal and figurative debt.